Design and analysis of nanoscale vertical MOSFET using oblique rotating implantation (ORI) method with reduced parasitic capacitance - Ismail, Razali (Amer Inst Physics, 2009)
The design and analysis of an enhanced performance of vertical MOSFET is revealed by adopting the oblique rotating ion implantation (ORI) method combined with fillet oxidation (FILOX) technology. These CMOS compatible processes have formed the symmetrical self-aligned source/drain regions over the silicon pillar with sharp vertical channel profiles. Accordingly, an increased numbers of electrons in the channel with decreased channel length (L(g)) have shown to improved the threshold voltage, sub-threshold swing, drive-on current, leakage current, DIBL and drain saturation current significantly. The drain overlap capacitance is a factor of 0.2 lower and the source overlap capacitance is a factor of 1.5 lower than standard vertical MOSFETs.